2021
DOI: 10.1101/2021.09.29.462384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bromodomain factor 5 is an essential transcriptional regulator of the Leishmania genome

Abstract: Leishmania are unicellular parasites that cause human and animal disease. Alongside other organisms in kinetoplastida, they have evolved an unusual genome architecture that requires all RNA polymerase II transcribed genes to be expressed constitutively, with transcriptional start regions denoted by histone variants and histone lysine acetylation. However, the way these chromatin marks are interpreted by the cell is not understood. Seven predicted bromodomain factors (BDF1-7), the reader modules for acetyl-lysi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…If an increase in acetylation levels and increased transcription are necessary during the transition from the quiescent stumpy form to the cycling procyclic form, this could result in the observed increase in Bdf3 occupancy following the differentiation cue. Bromodomain protein-mediated regulation of global Pol II transcript levels has been demonstrated in Leishmania ( 62 ). Transcriptome sequencing (RNA-seq) analyses are typically normalized in such a way as to obscure global increases or decreases in transcript levels ( 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…If an increase in acetylation levels and increased transcription are necessary during the transition from the quiescent stumpy form to the cycling procyclic form, this could result in the observed increase in Bdf3 occupancy following the differentiation cue. Bromodomain protein-mediated regulation of global Pol II transcript levels has been demonstrated in Leishmania ( 62 ). Transcriptome sequencing (RNA-seq) analyses are typically normalized in such a way as to obscure global increases or decreases in transcript levels ( 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our group has recently completed two projects where we extended the use of proximity biotinylation to understanding fundamental aspects of chromatin biology in Leishmania (Geoghegan et al, 2021;Jones et al, 2021). We firstly discovered that we could increase the capture of proximal proteins by performing a limiting DSP cross-linking step after proximity biotinylation, an approach we termed XL-BioID (Geoghegan et al, 2021).…”
Section: Leishmania Mexicanamentioning
confidence: 99%
“…According to the TriTrypDB (http://tritrypdb.org/tritrypdb/), there are seven coding sequences for BD-containing proteins in trypanosomatids, named Tc BDF1 to Tc BDF7. An eighth putative bromodomain factor recently identified in Leishmania spp has an orthologue in T. cruzi 8 . Even though a few Tc BDFs have recognizable additional domains the architecture of these proteins seems to be simpler than those of BD-containing proteins from fungi and animals, and none contains histone acetyltransferase (HAT) domains, as occurs in at least one bromodomain-containing protein from almost all eukaryotic cells including many protists.…”
Section: Introductionmentioning
confidence: 99%
“…Even though a genome-wide RNA interference viability screen showed that Tb BDF2 was not essential, it was found essential in another assay 46 . Very recently, Jones et al showed that five BDFs, among them BDF2, are essential for Leishmania mexicana promastigotes 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation